Exploratory Research on the Use of Energy Recovery Technology in Sewage Treatment in Indonesia - Irdam Irdam; Rakhmad Armus; Abdul Tahir; Kushariyadi Kushariyadi; Tungga Bhimadi Karyasa (West Science Interdisciplinary Studies, 2024)
This research delves into the integration of Energy Recovery Technology (ERT) within sewage treatment processes in Indonesia, addressing the imperative for sustainable wastewater management amid rapid population growth and urbanization. Through a comprehensive investigation encompassing technological, economic, and environmental dimensions, the study identifies challenges, evaluates the feasibility of ERT integration, and bridges critical gaps in the existing literature. The potential synergy between wastewater treatment and energy recovery aligns with Indonesia's commitment to sustainable development. The findings serve as a catalyst for innovative sewage treatment approaches, contributing to a paradigm shift in Indonesia's wastewater management practices. The accompanying bibliometric analysis provides a detailed overview of the academic landscape, key contributors, and impactful studies, enhancing the study's depth and practical implications.